Pendampingan Penerapan Teknologi Hand Tractor Sebagai Upaya Untuk Meningkatkan Hasil Produksi Pertanian Kelompok Tani Desa Sidomulyo - Achmad Rijanto; Suesthi Rahayuningsih; Luki Ardiantoro (CV. Multi Kreasi Media, 2024)
The partner for community service activities within the scope of Community Partnership Empowerment was the Farmers Group with the name Margo Rukun Farmers Group which was located in Seno hamlet, Sidomulyo village, Mojokerto district, East Java province. The partner location was approximately 3.7 km to the east of the Majapahit Islamic University. The problem faced by partners in the production sector was that partners still do not have agricultural machinery in the form of hand tractors, so partners are forced to rent hand tractors when cultivating agricultural land. This increases the burden on production costs, which results in higher production costs. The solution implemented was to provide a grant for 1 unit of hand tractor and provide knowledge and skills on how to operate a hand tractor. The method used in this service activity was providing assistance to farmer groups in the form of providing a grant of 1 unit of hand tractor and providing knowledge and skills on how to operate a hand tractor. The results of this community service activity were that 1) the partner has 1 additional agricultural machine tool asset in the form of a hand tractor, 2) the partner has additional knowledge and skills on how to operate a hand tractor, and 3) the partner does not need to pay rental fees for hand tractors, so that production costs decrease. With these three efforts, the agricultural production of farmer groups has increased.